Sustainable sorbitol-derived compounds for gelation of the full range of ethanol–water mixtures. Issue 19 (6th May 2020) - Dizon, Glenieliz C.; Atkinson, George; Argent, Stephen P.; Santu, Lea T.; Amabilino, David B.
Abstract : A combination of gelators prepared from sustainable sources combine in a synergic way to widen the scope for the compounds to immobilise liquids, as shown by imaging, diffraction and rheology measurements. Abstract : During the development of soft material systems inspired by green chemistry, we show that naturally occurring starting materials can be used to prepare mono- and di-benzylidene sorbitol derivatives. These compounds gelate a range of organic, aqueous (including with mono and divalent metal salt solutions) and ethanolic (ethanol–water) solutions, with the equimolar mixture of two of the gelators gelling all compositions from 100% ethanol to 100% water (something neither of the individual components do). We explored the influence of modifications to the acetal substituents on the formation of the compounds as well as the impact of steric bulk on self-assembly properties of the gelators. The effect of solvent on the self-assembly, morphology, and rheology of the 1, 3:2, 4-di(4-isopropylbenzylidene)-d -sorbitol (DBS-iPr), 2, 4(4-isopropylbenzylidene)-d -sorbitol (MBS-iPr) and the equimolar multicomponent (DBS–MBS-iPr) gels have been investigated. DBS-iPr gelates polar solvents to form smooth flat fibres, whereas in non-polar solvents such as cyclohexane helical fibres grow where the chirality is determined by the stereochemistry of the sugar. Oscillatory rheology revealed that MBS-iPr gels have appreciable strength and elasticity, in comparison to DBS-iPr gels, regardless of the solvent medium employed. Powder X-ray diffraction was used to probe the arrangement of the gelators in the xerogels they form, and two single crystal X-ray structures of related MBS derivatives give the first precise structural information concerning layering and hydrogen bonding in the monobenzylidene compounds. This kind of layering could explain the apparent self-sorting behaviour of the DBS–MBS-iPr multicomponent gels. The combination of sorbitol-derived gelators reported in this work could find potential applications as multicomponent systems, for example, in soft materials for personal care products, polymer nucleation/clarification, and energy technology.